Computed tomography, radiology and echocardiography in cats naturally infected with Aelurostrongylus abstrusus. Issue 4 (April 2017) - Lacava, Giuseppe; Zini, Eric; Marchesotti, Federica; Domenech, Oriol; Romano, Francesca; Manzocchi, Simone; Venco, Luigi; Auriemma, Edoardo
Objectives: The aims of the study were to describe the radiographic and computed tomographic features in cats naturally infected with Aelurostrongylus abstrusus, and to identify signs of pulmonary hypertension with echocardiography. Methods: Fourteen cats positive on Baermann test for A abstrusus were included in the study. All cats underwent thoracic radiography, CT and echocardiography. Results: The most common clinical signs were coughing (10/14) and dyspnoea (5/14). Radiographic findings included a generalised unstructured interstitial pulmonary pattern (8/14), mixed bronchointerstitioalveolar pattern (3/14) and bronchointerstitial pattern with bronchial wall thickening (3/14). Sternal lymphadenopathy was detected on thoracic radiographs in six cats. On CT, features were mixed bronchointerstitioalveolar pattern with ground-glass appearance in six cats, interstitioalveolar with multiple pulmonary nodules in five, interstitial ground-glass infiltrates in three, regional lymph node enlargement in 11 (10 sternal, three cranial mediastinal and three tracheobronchial lymph nodes) and subpleural thickening in four. None of the thoracic radiographs revealed subpleural thickening. In all cases, pulmonary vessels were normal in terms of size, shape and attenuation on both radiography and CT. Pulmonary hypertension and cardiac abnormalities were not observed in any cat during echocardiography. Conclusions and relevance: CT provided a more thorough characterisation of pulmonary and mediastinal lesions compared with thoracic radiographs in cats naturally infected with A abstrusus . Although feline aelurostrongylosis has been previously associated with histopathological lesions in lung arteries, in this cohort clinical evidence of pulmonary hypertension was not documented.